APPLICATION PROBLEM SOLVING METHOD ON CIRCLE EQUATIONS IN SENIOR HIGH SCHOOL BANDA ACEH - Mazidah Mazidah (Prodi Tadris Matematika Universitas Muhammadiyah Aceh, 2022)
This study aims to determine the increase in student learning outcomes, student learning completeness and student responses to problem solving methods on the circular equation material in class XI SMA Negeri Banda Aceh. The samples in this study were students of class XI IA-2 SMA Negeri 11 Banda Aceh in the 2014/2015 academic year, totaling 22 students. Data collection techniques used are observation, tests and questionnaires. Student learning outcomes test data were analyzed by right-hand t-test at a significant level = 0.05 with degrees of freedom (n 1) the test criteria Ho is accepted if tcount ttable. Meanwhile, student learning completeness and student responses were analyzed by percentage. Based on the results of data analysis obtained tcount ttable that is 25.11 1.72 so that Ho is rejected. Completeness of student learning is 86% and achieve classical completeness. The average score of student responses to the application of problem solving methods on the circular equation material is 3.52. Then the student's response is in very positive criteria. The conclusion of this study is that the application of problem solving methods to the circular equation material can improve student learning outcomes in class XI SMA Negeri 11 Banda Aceh